2022
DOI: 10.3389/fonc.2022.1016894
|View full text |Cite
|
Sign up to set email alerts
|

Radioresistance in rhabdomyosarcomas: Much more than a question of dose

Abstract: Management of rhabdomyosarcoma (RMS), the most common soft tissue sarcoma in children, frequently accounting the genitourinary tract is complex and requires a multimodal therapy. In particular, as a consequence of the advancement in dose conformity technology, radiation therapy (RT) has now become the standard therapeutic option for patients with RMS. In the clinical practice, dose and timing of RT are adjusted on the basis of patients’ risk stratification to reduce late toxicity and side effects on normal tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 254 publications
0
2
0
Order By: Relevance
“…Multiagent chemotherapy (vincristine, actinomycin D, and cyclophosphamide or ifosfamide) followed by radiotherapy represents the standard treatment of RMS patients. Although this approach results in >70% overall 5-year survival for localized tumors, intrinsic or acquired radioresistance is a predictor of poor (less than 30%) survival [ 2 , 3 ]. Deregulation of receptor tyrosine kinase (RTK) signaling through the RAS/extracellular signal-regulated kinases (ERK) and serine/threonine Akt/mammalian target of rapamycin (mTOR) pathways plays a key role in the pathogenesis of RMS [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiagent chemotherapy (vincristine, actinomycin D, and cyclophosphamide or ifosfamide) followed by radiotherapy represents the standard treatment of RMS patients. Although this approach results in >70% overall 5-year survival for localized tumors, intrinsic or acquired radioresistance is a predictor of poor (less than 30%) survival [ 2 , 3 ]. Deregulation of receptor tyrosine kinase (RTK) signaling through the RAS/extracellular signal-regulated kinases (ERK) and serine/threonine Akt/mammalian target of rapamycin (mTOR) pathways plays a key role in the pathogenesis of RMS [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Src-mediated phosphorylation of Cav1 on tyrosine-14 activates a variety of pathways related to cancer aggressiveness, influencing cell migration, invasion, and resistance to oxidative stress [ 21 , 22 ]. In recent years there has been growing interest in the mechanisms underlying radiation resistance in RMS [ 3 ]. In previous works, we demonstrated that increases in Cav1 and Akt levels support radioresistance [ 9 , 23 ].…”
Section: Introductionmentioning
confidence: 99%